(untitled) (Journal of the Association for the Study of Australian Literature, 2014)
In ’The Middle Parts of Fortune’ (1929)—perhaps the best narrative of the Great War—Australian author Frederic Manning asserted that ‘there was nothing in war which was not in human nature’ (128). Eighty years after Manning, in ’Ransom’ (2009), Malouf returns to the classical world to give us an emotive, complex consideration of the events which provide the basis for Western civilisation’s oldest surviving war narrative, ’The Iliad’. ’Ransom’ is not Malouf’s first exploration of war, though it marks a movement into a mythic rather than a liberal, realist interpretation. Through ’Fly Away Peter’ (1982) and ’The Great World’ (1990), we can trace Malouf’s multilayered exploration of the place of war in both individual story and cultural history. In particular, Malouf explores the ways in which war is both shocking and ordinary, delivering a complex appreciation of this recurring aspect of human experience.